Urgensi Pembentukan Undang-Undang Tentang Pemerintah Digital Dalam Perspektif Hukum Tata Negara - Rusli, Rusli; Auliaurrahman, Auliaurrahman; Anshari, Nur (Journal of Education, Humaniora and Social Sciences (JEHSS), 2025)
The development of information technology has encouraged various countries to adopt digital-based government systems to improve efficiency, transparency and accountability of public services. In Indonesia, the implementation of the digital government concept has not been fully supported by a strong legal framework in the form of a law. Currently, digital government regulations are still scattered in various laws and regulations under the law, such as Presidential Regulations and Ministerial Regulations, which do not have the same legal force as laws and are vulnerable to changes and overlapping authorities. This research aims to analyze the urgency of establishing a Law on Digital Government from the perspective of constitutional law. The research method used is normative juridical with statutory and conceptual approaches. The results show that the formation of this law is very important to ensure legal certainty, strengthen the principle of the rule of law, and regulate the division of authority between institutions constitutionally. In addition, the existence of a digital government law will be a strong legal foundation for the protection of citizens' rights in the digital space and support the realization of good governance In addition, the existence of a digital government law will be a strong legal foundation for the protection of citizens' rights in the digital space and support the realization of good governance. Thus, an immediate and serious legislative initiative is needed from the government and the DPR to draft and discuss the Digital Government Bill in accordance with the principles of constitutional law and the dynamics of digital society in the modern era.